Elderly Respondent Characteristics Through BE-FAST Education for Early Stroke Detection - Ni Luh Putu, Inca Buntari Agustini; Israfil, Israfil; Ni Made, Ratih Comala Dewi; I Gusti Ngurah , Aryana; I Kadek, Miki Indra Bela; Ni Kadek, Nefi Widiastuti; Firman , Abdurrahman (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Stroke is the second leading cause of death and disability worldwide. The elderly represent a vulnerable group at high risk for stroke. Raising awareness of early detection is a crucial strategy to reduce the incidence and impact of stroke. One effective early detection tool is the BE-FAST method (Balance, Eyes, Face, Arm, Speech, Time). This community service aimed to assess the characteristics of elderly participants and promote early stroke detection through BE-FAST education using the POAC approach (Planning, Organizing, Actuating, Controlling). A total of 79 elderly participants were included. Health screenings were conducted, including blood pressure measurements and BE-FAST assessments. Results showed that 55.7% of participants had hypertension, 67.1% had difficulty moving limbs on one side of the body, 36.7% experienced visual disturbances, and 32.9% showed signs of facial droop or numbness. The BE-FAST method was effective in detecting early stroke signs with a sensitivity of 92%.This initiative demonstrated the feasibility and effectiveness of using BE-FAST education in community settings to empower the elderly in recognizing early stroke symptoms and minimizing associated risks